Post-Abortion Syndrome: A Critical Review of the Literature - Robins, Melanie (2013)
Background and Aim Unwanted pregnancy and abortion are common life events, with an estimated 1 in 5 women experiencing an abortion within their lifetime. Although abortion itself is a relatively minor, safe procedure with minimal physical impact, controversy exists regarding the psychological risks associated with the termination of a pregnancy. A key argument within this debate is whether or not there is such a phenomenon as post-abortion syndrome. Therefore, this study aimed to examine the literature to establish the core psychological needs of women who decide to terminate their pregnancy. Method and Summary of Findings This review has been conducted using a critical review methodology. Pro-life groups have cited the existence of a post-abortion syndrome to support their argument against abortion. However, evidence suggests there is not a specific set of psychological consequences attributed to abortion that can be legitimately gathered to form a recognisable syndrome. In spite of this, studies have consistently found a small percentage of women, between 8 and 32%, who do experience some sort of emotional distress following an abortion and various factors have been found to influence this. Conclusion The literature suggests that the majority of women will not suffer from prolonged psychological distress following an abortion. However, some women have been found to experience emotional difficulties and would therefore benefit from post-abortion support, which is impartial and non-judgemental, being made readily available.